(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Rao’s collection of short stories explores the tenuous place of women. Some of the stories stand independently, others are intertwined, with characters from one story popping up years later in another. An Unrestored Woman is Shobha Rao’s debut collection about the shared grief that occurred starting with the 1949 partition of India and Pakistan. Rao’s historical fiction has likewise gives a voice to top to bottom, multi-layered characters has picked up inclusion in my women’s history month lineup. The paper in hand is a feministic study of two tales from Shobha Rao’s An Unrestored Woman and Other Stories. These stories move around female characters confronting embarrassment, and misuse in society. The stories under discussion are An Unrestored Woman and The merchant’s wife. The stories are described in the third person perspective. The language is fluid and real. The principle association between these stories is two protagonists and the intensity of their misery. The primary characters of these are Neela and Renu. They interacted with one another at the refugee camp where they were sent to live in their widowhood. These two stories are their experience to conquer the circumstances which were granted to them as a woman by the society. Renu and Neela persistently remind one another. It appears that writer as a narrator wants to analyze their sufferings. She wants to paint two diverse picture and simultaneously correlate them. Writer’s primary concern is to delineate women identity in society. The account of stories satisfies her purpose effectively.